"Every Change We Made on the Chip Was an Adventure": A portrait of Pim Kat, founder and former CEO of Technobis Group. Issue 4 (3rd August 2020) - Pozo, Jose
Abstract: EPIC's chief technology officer Jose Pozo had the opportunity to talk to Pim Kat, CTO of Technobis, one of the earliest adopters of integrated photonics for industrial applications in Europe.